2013
DOI: 10.4314/ajtcam.v10i5.17
|View full text |Cite
|
Sign up to set email alerts
|

<i>Gongronema Latifolium</i> delays gastric emptying of semi-solid meals in diabetic dogs

Abstract: The aim of the study was to investigate sonographically the effect of Gongronema latifolium on gastric emptying of semi-solid meals in diabetic dogs. Twenty-five alloxan-induced diabetic dogs were randomly allotted into five groups of five dogs each in a randomised placebo-controlled study. These are placebo, prokinetic dose, low dose, moderate dose and high dose groups. The placebo group served as the control. The low, moderate and high dose groups ingested methanolic leaf extract of G. latifolium at 100 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The application of plant-derived metabolites for the management of canine diabetes has been studied extensively ( Russell et al, 2008 ). Bixa orellana extract was reported to decrease the blood glucose level by increasing peripheral glucose utilization in streptozotocin-induced diabetic dogs ( Russell et al, 2008 ; Ogbu et al, 2013 ). Gongronema latifolium maintained the plasma glucose levels in alloxan-induced diabetic dogs by delaying stomach emptying ( Ogbu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of plant-derived metabolites for the management of canine diabetes has been studied extensively ( Russell et al, 2008 ). Bixa orellana extract was reported to decrease the blood glucose level by increasing peripheral glucose utilization in streptozotocin-induced diabetic dogs ( Russell et al, 2008 ; Ogbu et al, 2013 ). Gongronema latifolium maintained the plasma glucose levels in alloxan-induced diabetic dogs by delaying stomach emptying ( Ogbu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bixa orellana extract was reported to decrease the blood glucose level by increasing peripheral glucose utilization in streptozotocin-induced diabetic dogs ( Russell et al, 2008 ; Ogbu et al, 2013 ). Gongronema latifolium maintained the plasma glucose levels in alloxan-induced diabetic dogs by delaying stomach emptying ( Ogbu et al, 2013 ). Additionally, numerous medicinal plants are reported to have the potential to improve the management of diabetes in humans ( Bindu and Narendhirakannan, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect was attributed to an insulin-like activity of the ethanolic extract [ 23 ] and more recently an insulinotropic activity [ 22 ]. Ogbu , et al [ 46 ] attributed the decrease in BGLs partly to delayed gastric emptying. Our in vitro findings showed that GLES had no effect on glucose active transport via the intestinal wall.…”
Section: Discussionmentioning
confidence: 99%